2003
DOI: 10.1093/emboj/cdg349
|View full text |Cite
|
Sign up to set email alerts
|

The molecular chaperone Hsp90 plays a role in the assembly and maintenance of the 26S proteasome

Abstract: Hsp90 has a diverse array of cellular roles including protein folding, stress response and signal transduction. Herein we report a novel function for Hsp90 in the ATP-dependent assembly of the 26S proteasome. Functional loss of Hsp90 using a temperature-sensitive mutant in yeast caused dissociation of the 26S proteasome. Conversely, these dissociated constituents reassembled in Hsp90-dependent fashion both in vivo and in vitro; the process required ATP-hydrolysis and was suppressed by the Hsp90 inhibitor gelda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(151 citation statements)
references
References 25 publications
6
143
1
1
Order By: Relevance
“…Among the stable PIPs, there are three types of chaperone proteins including heat shock protein and components of the AP-3 and CCT complexes. Consistent with these findings, various heat shock proteins have been shown to interact with yeast proteasomes (7,15) and were suggested to facilitate delivery of aggregation-prone substrates for degradation (30,32) or to play a role in the proteasome structural integrity and assembly (31). In contrast, the interactions of the AP-3 and CCT complexes with the human proteasomes have not been reported before.…”
Section: -H Map-silacmentioning
confidence: 57%
“…Among the stable PIPs, there are three types of chaperone proteins including heat shock protein and components of the AP-3 and CCT complexes. Consistent with these findings, various heat shock proteins have been shown to interact with yeast proteasomes (7,15) and were suggested to facilitate delivery of aggregation-prone substrates for degradation (30,32) or to play a role in the proteasome structural integrity and assembly (31). In contrast, the interactions of the AP-3 and CCT complexes with the human proteasomes have not been reported before.…”
Section: -H Map-silacmentioning
confidence: 57%
“…Studies, primarily with animals, have revealed that Hsp90 plays roles in a diverse array of cellular processes including protein folding, stress responses, signal transduction, and genomic silencing. Recent studies show that Hsp90 also plays a critical role in the ATP-dependent assembly of the 26 S proteasome (17). Other studies suggest that Hsp90 acts as a buffer against genetic variation as a capacitor of phenotypic variation in plants as in fruit flies (18,19).…”
mentioning
confidence: 99%
“…56 These findings may provide new mechanistic insight into the cooperative interactions between the molecular chaperone and proteolysis systems. In the same study, we found that in vivo and in vitro inactivation of Hsp90 caused dissociation of the 26S proteasomes into their constituents.…”
Section: Molecular Chaperonesmentioning
confidence: 93%
“…63 Moreover, molecular chaperones, such as Hsp70 and Hsp90, are responsible for the maintenance of functional states of the UPS pathway, particularly the 26S proteasome as mentioned above. 56 These observations uncover a strong functional link between UPS and molecular chaperones.…”
Section: Perspectivesmentioning
confidence: 95%